Health Tourism and Aesthetic Surgery Clinics in Indonesia: Opportunities and Policy Frameworks - Arti Indira; Sandra Agna Setyo Budi; Rian Andriani (Jurnal Locus Penelitian dan Pengabdian, 2026)
Aesthetic surgery is an increasingly significant sector in health tourism, offering strong potential to boost Indonesia’s economic growth. With abundant natural resources, skilled medical professionals, and cost-effective healthcare, Indonesia is well-positioned as a medical tourism destination in Asia. However, the lack of comprehensive policies on international patient safety, absence of globally recognized clinical accreditation, and limited government-led promotion hinder full market potential. This research adopts a literature review approach guided by the PCC (Population, Concept, Context) framework to define scope and selection criteria. Sources were obtained from Google Scholar, Scopus, BMC, Sage Publications, and other credible databases, and screened collaboratively by the authors to ensure thematic relevance. The review highlights key opportunities for Indonesia’s aesthetic surgery sector, including market growth potential and increasing global demand, while identifying critical gaps in accreditation systems, standardized service protocols, patient safety measures, and coordinated promotional strategies. Strengthening Indonesia’s competitiveness requires integrated collaboration between health, tourism, and regulatory sectors. Implementing robust policy frameworks, aligning with global standards, and investing in targeted international marketing will be crucial to positioning Indonesia as a safe, high-quality, and competitive destination within Southeast Asia’s health tourism landscape.